Urban settlement: Data, measures, and trends - David E. Bloom; David Canning; Günther Fink; Tarun Khanna; Patrick Salyer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper examines data on urbanization. We review the most commonly used data sources, and highlight the difficulties inherent in defining and measuring the size of urban versus rural populations. We show that differences in the measurement of urban populations across countries and over time are significant, and discuss the methods used to obtain these measurements, as well as those for projecting urbanization. We also analyze recent trends and patterns in urbanization. Finally, we describe the principal channels of urbanization and examine their relative contributions to the global urbanization process.
Keywords: O18; R11; 330; urbanization; measurement; urban population; Urbanisierung; Städtische Bevölkerungsentwicklung; Bevölkerungsdichte; Messung; Vergleich; Welt